ASSESMENT OF ATTITUDE AND PRACTICE TOWARDS ADVERSE DRUG REACTION REPORTING OF HEALTH PROFESSIONALS IN REPUBLIC OF NORTH MACEDONIA - Kokolanski, Vlatko; Zafirov, Dimche; Danevska, Marijana; Ivanovski, Kjiro; Nikolovska, Julijana; Spasovski, Spiro; Poposki, Bojan (Journal of Morphological Sciences; Vol 7 No 2 (2024): JMS, 2024)
There is no drug that can be declared completely safe. The application of any medicine carries the potential risk of adverse drug reactions. Pharmacovigilance is central to reducing adverse drug reactions, so the development and growth of this science is critical for effective and safe clinical practice. The aim of this study is to determine the extent of ADR reporting, the attitude and associated factors about the national pharmacovigilance system among healthcare professionals. 400 health professionals were included in this study (100 doctors of medicine, 100 doctors of dental medicine, 100 pharmacists and 100 medical nurses/technicians) employed in public and private healthcare institutions in the city of Skopje, by using anonymous survey questionnaire. The majority of respondents included in our research believe that it is necessary to report adverse drug reactions, and that health professionals need to be familiar with the pharmacovigilance system. The percentage of registered but unreported ADRs, in our research, is 47.29%, where the highest number of health professionals consider the difficulty to determine whether there is an adverse drug reaction or not as the main factor that determines whether they report an ADR. This study showed that majority of the healthcare professionals had positive attitude regarding pharmacovigilance, and they understand the need for reporting adverse drug reactions,.However, the rate of reported ADRs is very low. Keywords: pharmacovigilance, attitude, adverse drug reactions, healthcare proffesionals.